Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Guru SMPN 2 Cikampek - Pujiantoro, Azhar Abisya; Suroso, Suroso; Anggela, Flora Praticia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to examine how the work environment and work motivation influence teacher performance at SMPN 2 Cikampek. The research method uses a quantitative approach involving 38 teachers at SMPN 2 Cikampek as research respondents by applying a saturated sample. Data analysis was carried out using multiple linear regression using F and t-tests with a significance level of 5%. The research results show that the work environment (X1) does not affect the performance of SMPN 2 Cikampek teachers with a value of 1,147 < 2,301. Meanwhile, work motivation (X2) has a very significant effect on teacher performance at SMPN 2 Cikampek with a value of 4,834 > 2,301. Simultaneously, the work environment and work motivation together influence the level of teacher performance (Y) as shown by the calculated F value of 20,508 > 3.26. The influence of the work environment and work motivation on teacher performance at SMPN 2 Cikampek is 54% while the remaining 46% is influenced by other factors not examined in this research.